Isolated central nervous system relapse in blast crisis of chronic myeloid leukemia: a case report - Hari Priya Raghvan; Caroline Ho Siew Ling; Wee Shiang Yui; Boo Yang Liang; Ehram Jamian; Indhira Subbiah (Journal of Yeungnam Medical Science)
Chronic myeloid leukemia (CML) typically progresses from a chronic phase to an accelerated phase, and eventually to a blast crisis, often involving the bone marrow and peripheral blood, if left untreated. Central nervous system (CNS) involvement is an uncommon manifestation of CML, particularly as an isolated CNS relapse. Here, we present a rare case of CML in lymphoid blast crisis with an isolated CNS relapse. A 46-year-old female with underlying CML in lymphoid blast crisis, previously treated with chemotherapy and tyrosine kinase inhibitors, presented with visual disturbances. Imaging and cerebrospinal fluid analysis confirmed leukemic infiltration of the CNS without evidence of a systemic disease. Isolated CNS involvement is an atypical complication of CML and presents significant therapeutic challenges owing to the blood-brain barrier, which limits the efficacy of systemic therapies. Subsequently, the patient was treated with intrathecal chemotherapy targeting the CNS. Despite aggressive treatment, CNS relapse remains a major concern due to the limited penetration of standard therapies into the CNS. This case underscores the importance of early recognition of CNS symptoms in CML patients, particularly in those with blast crisis, and highlights the need for tailored therapeutic strategies to manage this rare and challenging manifestation.